Critical Discourse of Social Space in Urban Sustainable Development: A Neo-Marxian Social-spatial Political Perspective - Geraldy, Galang (Universitas Brawijaya, 2024)
The Sustainable Development Goals (SDGs) have grown prevalent in development discourse across numerous cities, incorporating economic, ecological, and social aspects. The critical discourse on social space in urban sustainable development, viewed through the lens of neo-Marxian socio-spatial politics, underscores the intricate interplay among space, power, and economy within the urban environment. The language of the SDGs is examined through the lens of capitalist economic frameworks and power dynamics in the development of urban environments. Sustainable development frequently entails intricate conflicts of interest among diverse stakeholders, including governments, corporations, local communities, and civil society organizations. Figures such as Henry Lefebvre and David Harvey engage in neo-Marxian social-spatial political critique. Manuel Castell and Edward Soja emphasize that power and spatial control frequently engender conflict through the commodification of space, illustrating that urban and rural areas are often regarded as commodities for economic profit, leading to gentrification, forced evictions, and social alienation. Economic and social disparities are manifested in spatial inequalities within urban development. Neo-Marxist socio-spatial political theorists emphasize equality, social justice, and individuals' rights to urban space. The research of SDGs is predominantly focused on the junction of economic and ecological mutualism, rather than sufficiently addressing the social and spatial components. This neo-Marxian social-spatial political approach elucidates the complexities and inequities inherent in urban development, providing an analytical framework to comprehend and tackle the issues associated with attaining sustainable and inclusive urban growth.